2014
DOI: 10.3390/s141018543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Characterization of Android-Based Fall Detection Systems

Abstract: Falls are a foremost source of injuries and hospitalization for seniors. The adoption of automatic fall detection mechanisms can noticeably reduce the response time of the medical staff or caregivers when a fall takes place. Smartphones are being increasingly proposed as wearable, cost-effective and not-intrusive systems for fall detection. The exploitation of smartphones' potential (and in particular, the Android Operating System) can benefit from the wide implantation, the growing computational capabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 76 publications
0
48
0
Order By: Relevance
“…Moreover, studies demonstrated that samples from smartphones sensors (e.g., accelerometer and gyroscope) are accurate enough to be used in clinical domain, such as ADLs recognition [22]. This is also confirmed by the amount of publications that rely on the use of smartphones as acquisition devices for fall detection systems [18,23] and ADLs recognition.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, studies demonstrated that samples from smartphones sensors (e.g., accelerometer and gyroscope) are accurate enough to be used in clinical domain, such as ADLs recognition [22]. This is also confirmed by the amount of publications that rely on the use of smartphones as acquisition devices for fall detection systems [18,23] and ADLs recognition.…”
Section: Introductionmentioning
confidence: 69%
“…Recently, a lot of attention has been paid to wearable sensors because they are less intrusive, work outdoors, and often cheaper than the ambient ones. This is confirmed by the increasing number of techniques that are based on wearable sensors (see for example the survey by Luque et al related to fall detection techniques relying on data from smartphones [18]). …”
Section: Introductionmentioning
confidence: 81%
“…Recently, a lot of attention has been paid to wearable sensors because they are less intrusive, work outdoors, and often cheaper than the ambient ones. This is confirmed by the increasing number of techniques that are based on wearable sensors (see for example the survey by Luque et al related to fall detection techniques relying on data from smartphones [13]).…”
Section: Introductionmentioning
confidence: 81%
“…The first group analyses the vital signs provided by wearable sensors (Banaee et al, 2013) such as electrocardiogram, oxygen saturation, heart rate, photoplethysmography, blood glucose, blood pressure and respiratory rate. The second group is focused on recognising and monitoring individual human activities (Liao et al, 2005;Luque et al, 2014;Vilarinho et al, 2015;Micucci et al, 2017;Kulev et al, 2016), which also overlaps with the fields of computer vision, machine learning and data mining. Our study in this paper is closer to the second group.…”
Section: Related Workmentioning
confidence: 99%